2022
DOI: 10.1108/cr-12-2021-0188
|View full text |Cite
|
Sign up to set email alerts
|

The return volatility and shock transmission patterns of chosen S&P and Dow Jones sustainability indices and their conventional counterpart

Abstract: Purpose The purpose of this study is to investigate the dynamic return volatility connectedness among S&P, Dow Jones (DJ) sustainability indices and their conventional counterparts. Design/methodology/approach This study uses time-series daily data for 10 S&P and DJ indices over the period of December 1, 2012 to December 8, 2021. The authors divide the data into three periods; over the whole sample, pre and during the Covid-19 pandemic. The study adopts the connectedness approach developed by Diebold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the country-level variables, we include country governance and gross domestic product (GDP) growth. The tax-free countries are a preferred destination for foreign direct investment; hence, the country governance, legal and regulatory environment present a key determinant for the FDI attrition and retention (Almansour et al. , 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the country-level variables, we include country governance and gross domestic product (GDP) growth. The tax-free countries are a preferred destination for foreign direct investment; hence, the country governance, legal and regulatory environment present a key determinant for the FDI attrition and retention (Almansour et al. , 2023).…”
Section: Methodsmentioning
confidence: 99%
“…In the country-level variables, we include country governance and gross domestic product (GDP) growth. The tax-free countries are a preferred destination for foreign direct investment; hence, the country governance, legal and regulatory environment present a key determinant for the FDI attrition and retention (Almansour et al, 2023). Hence, strong and efficient country governance (six proxies, including the voice and accountability; political stability and absence of violence/terrorism; government effectiveness; regulatory quality; the rule of law and control of corruption) reduces firms' management's incentive to conduct EM and enhance the financial reports stockholders' confidence (Kanagaretnam et al, 2014).…”
Section: Earnings Managementmentioning
confidence: 99%
“…This study reached many results, the most important of which is that it revealed a negative relationship between environmental disclosure and the performance of banks, lending credence to the agency and neoclassical theories. Almansour et al (2022) investigate the dynamic return volatility connectedness among S&P, Dow Jones (DJ) sustainability indices and their conventional counterparts. The results show that there is a high degree of correlation between the S&P and DJ indices and their relative sustainability indexes over the entire sample (December 1, 2012 to December 8, 2021) before and during the Covid-19 pandemic.…”
Section: Lecturer and Special Issue Reviewmentioning
confidence: 99%
“…ESG has obtained a lot of attention and support in recent years both in terms of ESG disclosures and ESG investments, especially during the Covid-19 pandemic, as ESG funds outperformed traditional funds (Takahashi and Yamada, 2020). Almansour et al (2022) found that S&P and Dow Jones sustainability indices are highly connected, and during the pandemic, conventional indices were shock transmitters, while the sustainability indices were the receivers of shock. The world's largest asset management company BlackRock also urged companies to publish better ESG disclosures rather than waiting for regulatory compliance (BlackRock, 2021).…”
mentioning
confidence: 99%